2017
DOI: 10.1002/1873-3468.12671
|View full text |Cite
|
Sign up to set email alerts
|

Tonoplast (BvTIP1;2) and plasma membrane (BvPIP2;1) aquaporins show different mechanosensitive properties

Abstract: Previous works proposed that aquaporins behave as mechanosensitive channels. However, principal issues about mechanosensitivity of aquaporins are not known. In this work, we characterized the mechanosensitive properties of the water channels BvTIP1;2 (TIP1) and BvPIP2;1 (PIP2) from red beet (Beta vulgaris). We simultaneously measured the mechanical behavior and the water transport rates during the osmotic response of emptied-out oocytes expressing TIP1 or PIP2. Our results indicate that TIP1 is a mechanosensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…This gating mechanism would be cooperative, maybe involving the four monomers of the tetramer (Ozu et al 2013). In addition, sensitivity differences could exist between PIPs and TIPs (Goldman et al 2017). Taken together, this evidence suggests that this mechanism would have existed before divergence of PIP-AQP1like and TIP-AQP8-like AQPs.…”
Section: Gatingmentioning
confidence: 83%
See 1 more Smart Citation
“…This gating mechanism would be cooperative, maybe involving the four monomers of the tetramer (Ozu et al 2013). In addition, sensitivity differences could exist between PIPs and TIPs (Goldman et al 2017). Taken together, this evidence suggests that this mechanism would have existed before divergence of PIP-AQP1like and TIP-AQP8-like AQPs.…”
Section: Gatingmentioning
confidence: 83%
“…These and other experimental evidence (Niemietz and Tyerman 1997) suggested that cell volume or pressure could be directly involved in the regulation of AQPs under hyper-and hypoosmotic conditions. Recently, mechanical gating has been probed as a possible mechanism in hAQP1 (Ozu et al 2013) and VvTIP2;1 (Leitão et al 2014), and experimentally probed for BvTIP2;1 (Goldman et al 2017). This gating mechanism would be cooperative, maybe involving the four monomers of the tetramer (Ozu et al 2013).…”
Section: Gatingmentioning
confidence: 99%
“…Experimental demonstration for the tension-mediated regulation in animal and plant AQPs was reported by simultaneous measurements of mechanical coefficients and water transport rates in proteoliposomes with RnAQP4 (rat) [ 134 ] and Xenopus oocytes expressing BvTIP1;2 (beet) [ 135 ]. In both cases, the water permeability coefficient decreases in a nonlinear fashion with increments of membrane elasticity, as was predicted for AQP1 [ 38 ].…”
Section: Structural Changes That Regulate Permeationmentioning
confidence: 99%
“…As widely reported on revisions, MS ion channels activate (open) with increasing tension [ 136 , 137 , 138 , 139 ]. On the contrary, MS AQPs (AQP4, AQP1, BvTIP1;2, VvTIP2;1) decrease their water transport rate when membrane tension raises, evidencing a closure event of the water pathway [ 38 , 132 , 134 , 135 ]. However, it cannot be generalized since MD simulations performed with the structure of AQY1 from the yeast Pichia pastoris predict that this AQP would open when increasing membrane curvature [ 64 ].…”
Section: Structural Changes That Regulate Permeationmentioning
confidence: 99%
See 1 more Smart Citation